2014
DOI: 10.1007/s00787-013-0510-y
|View full text |Cite
|
Sign up to set email alerts
|

Striatal volume deficits in children with ADHD who present a poor response to methylphenidate

Abstract: Methylphenidate (MPH) is the first choice of medical treatment for attention-deficit/hyperactivity disorder (ADHD). Its mechanism of action is to inhibit the reuptake of dopamine and noradrenaline mainly in the region of the striatum. It has been estimated that 10-30 % of patients with ADHD do not respond adequately to MPH. The aim of this study was to evaluate whether striatal differences exist between good and poor responders to MPH. The sample included 27 treatment-naïve children with ADHD between the ages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 43 publications
1
16
0
3
Order By: Relevance
“…Nonresponsive patients to MPH therapy can reach up to 30% of ADHD patients. The reasons for this unresponsiveness are still unknown and presently no clinical or biological markers have been found that could distinguish good from poor responders to MPH (Moreno et al, 2014). No responsiveness could reflect interindividual differences, namely very low DA activity, differences in the sensitivity or levels of DAT, differences in sensitivity of postsynaptic DA receptors and/or differences in the noradrenergic activity (Volkow et al, 2002, 2005).…”
Section: Methylphenidate (Mph)mentioning
confidence: 99%
See 2 more Smart Citations
“…Nonresponsive patients to MPH therapy can reach up to 30% of ADHD patients. The reasons for this unresponsiveness are still unknown and presently no clinical or biological markers have been found that could distinguish good from poor responders to MPH (Moreno et al, 2014). No responsiveness could reflect interindividual differences, namely very low DA activity, differences in the sensitivity or levels of DAT, differences in sensitivity of postsynaptic DA receptors and/or differences in the noradrenergic activity (Volkow et al, 2002, 2005).…”
Section: Methylphenidate (Mph)mentioning
confidence: 99%
“…This means that patients that do not respond adequately to MPH treatment are excluded from these studies. A recent study evaluated whether striatal differences exist between good and poor responders to MPH, in a sample that included 27 treatment‐naive children with ADHD aged between 6 and 14 (19 males and 8 females) (Moreno et al, 2014). After a month of MPH treatment, psychiatrists established that 16 patients showed good response to MPH and 11 a poor one.…”
Section: Methylphenidate (Mph)mentioning
confidence: 99%
See 1 more Smart Citation
“…No obstante, la muestra del estudio es reducida, por lo que estos resultados deben considerarse como pre liminares. Por último, otro estudio transversal con niños con TDAH llevado a cabo recientemente su giere la implicación de los núcleos caudado y accumbens no sólo en el control inhibitorio, sino tam bién en el funcionamiento atencional [19].…”
Section: Correlato Entre La Neuroanatomía Y La Neuropsicologíaunclassified
“…Los datos de estudios transversales asocian los síntomas de TDAH, ya sea de manera conjunta o por separado, con una relativa amplia variedad de regiones cerebrales. Mayores niveles de inatención también se han vinculado a nivel subcortical con el volumen de las regiones talámicas [28], núcleos caudado y accumbens [19], y cerebelo [29]. A nivel cortical, también se han encontrado relaciones en tre las regiones prefrontales y los síntomas de in atención [30].…”
Section: Correlato Entre La Neuroanatomía Y La Clínicaunclassified